Effect of rapeseed meal degraded by enzymolysis and fermentation on the growth performance, nutrient digestibility and health status of broilers. Issue 3 (2nd November 2022) - Li, Pei; Ji, Xiaoyu; Deng, Xuejuan; Hu, Siyu; Wang, Jianping; Ding, Ke; Liu, Ning
ABSTRACT: The purpose of this study is to investigate the nutritional changes of degraded rapeseed meal and its effects on growth performance, nutrient digestibility and health status of broilers. Raw rapeseed meal (CON), degraded by enzymolysis (protease, ERM), fermentation ( Bacillus subtilis, FRM) or both (DRM) were included in diets at 25% and fed to 480 yellow-feathered broilers at 22–63 d of age. Results showed that rapeseed peptide contents (≤1 kDa) were increased ( p < 0.05) from 4.13% (CON) to 35.5% (ERM), 24.1% (FRM) and 50.4% (DRM); glucosinolate and erucic acid in DRM were decreased ( p < 0.05) by 71.6% and 86.2%, respectively, compared to CON. There were increases ( p ≤ 0.029) in feed intake, body weight gain, feed efficiency and precaecal digestibility of dry matter, crude protein, methionine, isoleucine, leucine, lysine, cysteine, phenylalanine, tyrosine, threonine, tryptophan and valine in the three degraded diets. Also, serum immunoglobulin (Ig) A, IgG, glutathione peroxidase, superoxide dismutase and catalase were raised ( p ≤ 0.034) in the degraded diets. Additionally, DRM showed more pronounced effects ( p < 0.05) on variables related to growth, digestibility and health than ERM and FRM. It is concluded that rapeseed meal degraded by both enzymolysis and fermentation can increase its nutritional values and application in broilers.